Hate crime in Turkey implications of collective action, media representations and policy making - Göktan, Deniz Ünan (Newcastle upon Tyne : Cambridge Scholars Publishing, 2017)
This book examines how hate crime, as a contemporary legal concept, is introduced and represented in Turkish public discourse. The study addresses questions of how effective the hate crime debate in Turkey has been in identifying bias-motivated violent incidents and how social institutions perceive hate crimes and influence the related debates instigated by social movement actors.First of all, the study explores the movement against hate crime in Turkey, and argues that hate crime has operated as an umbrella term, diverting distinct identity movements into dialogue and collaboration, but has a.
Table of Contents; Preface; Acknowledgements; List of Abbreviations; Introduction; Chapter One; Chapter Two; Chapter Three; Chapter Four; Chapter Five; Chapter Six; Chapter Seven; Chapter Eight; Conclusion; Bibliography; Appendices
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed November 2, 2017).
Master record variable field(s) change: 050, 072, 650
Keywords: Hate crimes -- Turkey; SOCIAL SCIENCE / Criminology; Electronic books